2006
DOI: 10.1063/1.2405885
|View full text |Cite
|
Sign up to set email alerts
|

Stress dependence of ferromagnetic resonance and magnetic anisotropy in a thin NiMnSb film on InP(001)

Abstract: The authors have investigated the effect of stress on the room-temperature magnetism of a 10nm thick Heusler-alloy film NiMnSb grown epitaxially on InP. Tensile stress, which the authors applied externally along the easy axis using a piezostack, is shown to reduce the coercivity and the anisotropy coefficient. Using broadband ferromagnetic resonance measurements, the authors find that a relative variation in the lattice constant as small as 0.08% changes the in-plane uniaxial anisotropy by 20%. This explains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…This approach has already been shown to allow in-situ manipulation of magnetic anisotropy in piezoelectric actuator/ferromagnet hybrid samples at room temperature. 48,49 We have recently demonstrated that this approach can be transferred to piezoelectric actuator/GaMnAs hybrids, 50 as also reported by Refs. 51 and 52.…”
Section: Introductionmentioning
confidence: 72%
“…This approach has already been shown to allow in-situ manipulation of magnetic anisotropy in piezoelectric actuator/ferromagnet hybrid samples at room temperature. 48,49 We have recently demonstrated that this approach can be transferred to piezoelectric actuator/GaMnAs hybrids, 50 as also reported by Refs. 51 and 52.…”
Section: Introductionmentioning
confidence: 72%
“…For instance, various nanoelectromechanical and energy harvesting devices employing wurtzite II–VI and III–V semiconductor compounds have recently been demonstrated1. At the same time, nanocomposite23 or hybrid45 piezoelectric/magnetic systems allow for the electric control of magnetization.…”
mentioning
confidence: 99%
“…In this configuration, an electric field changes the elastic strain provided by the underlayer, which modifies the magnetic anisotropy [13] and correspondingly the spin-wave properties of the ferromagnet. Piezoelectrically controlled ferromagnetic resonance has already been established [14,15]. Magnonic devices might be even further advanced using reprogrammable states provided by coupling to ferroelastic domains of a ferroelectric substrate or underlayer.…”
Section: Introductionmentioning
confidence: 99%